2014
DOI: 10.14260/jemds/2014/2075
|View full text |Cite
|
Sign up to set email alerts
|

Full Term Extrauterine Abdominal Pregnancy

Abstract: Extrauterine abdominal pregnancy is extremely rare and is frequently missed during antenatal care, despite the routine use of obstetrics ultrasound. A 23 year old primigravida at 39 weeks of gestation was admitted to the department on December 2, 2012, in routine hour with transverse lie with oligohydramnios. On examination her vitals and laboratory investigation were within normal limits. One of the ultrasonographic scanning done by radiologist at 35 wk. 3 days gestation demonstrated a single live intrauterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…20 It has been extensively reported that blastocysts can implant in the uterus as well as in a wide variety of ectopic sites such as the broad ligament, omentum, and bowel, with reported successful term pregnancies in humans. [21][22][23] However, in contrast to the uterus, implantation occurs in ectopic sites regardless of hormonal conditioning, 20 highlighting that the uterus is the major controlling partner in the implantation process through the window of implantation (WOI) which corresponds to the critical window in the menstrual cycle that determines whether implantation can occur or not (►Fig. 1B).…”
Section: Recurrent Implantation Failurementioning
confidence: 99%
“…20 It has been extensively reported that blastocysts can implant in the uterus as well as in a wide variety of ectopic sites such as the broad ligament, omentum, and bowel, with reported successful term pregnancies in humans. [21][22][23] However, in contrast to the uterus, implantation occurs in ectopic sites regardless of hormonal conditioning, 20 highlighting that the uterus is the major controlling partner in the implantation process through the window of implantation (WOI) which corresponds to the critical window in the menstrual cycle that determines whether implantation can occur or not (►Fig. 1B).…”
Section: Recurrent Implantation Failurementioning
confidence: 99%